2016
DOI: 10.1108/imr-05-2014-0179
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing destination choices: the role of economic and cultural attributes

Abstract: Purpose – The purpose of this paper is to examine how country-of-origin (COO) perceptions of managers affect their provider selection for offshoring and offshore-outsourcing of services. In particular, it examines how economic and cultural attributes of the supplier’s host nation shape these choices and identifies whether these attributes have a substitutive, complementary, or competing relationship. Design/methodology/approach – A quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 134 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…Taking into account the role religion plays in the daily activities of Islamic businesses and Muslim consumers, the growing number of publications looks into interactions between marketing principles and Islamic values (Khan et al , 2015; Oyedele and Firat, 2018; Livanis et al , 2016; Shaikh et al , 2018). In particular, researchers emphasise the role of Islamic ethics, which offers to businesses its own marketing practice prescriptions and shapes government policies and corporate decisions (Ali and Al-Aali, 2015; Ali et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taking into account the role religion plays in the daily activities of Islamic businesses and Muslim consumers, the growing number of publications looks into interactions between marketing principles and Islamic values (Khan et al , 2015; Oyedele and Firat, 2018; Livanis et al , 2016; Shaikh et al , 2018). In particular, researchers emphasise the role of Islamic ethics, which offers to businesses its own marketing practice prescriptions and shapes government policies and corporate decisions (Ali and Al-Aali, 2015; Ali et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can also be a civilization of certain nations. Culture also emerges from the development and improvement of the mind by education or training [56]. Technology has redefined the boundaries of culture and has resulted in the emergence of e-culture [57].…”
Section: Sociocultural Factors and Soft Drink Anticonsumption Behaviormentioning
confidence: 99%
“…For example, Chung and Yeaple (2008) determined that industry similarity with regards to technology as well as a relative knowledge-surplus in the host country determines the offshoring choices of companies. Livanis et al (2016) suggested that the offshoring destination choice may be influenced by managers’ perceptions of the economic and cultural attributes of the supplier’s host nation. Kshetri and Dholakia (2009) found that the existence of professional and trade organizations stimulates offshore activities.…”
Section: Literature Reviewmentioning
confidence: 99%